Weekly adalimumab treatment decreased disease flare in hidradenitis suppurativa over 36 weeks: integrated results from the phase 3 PIONEER trials. (19th November 2019) - van der Zee, H.H.; Longcore, M.; Geng, Z.; Garg, A.
Abstract: Background: Hidradenitis suppurativa (HS) is a chronic skin disease characterized by inflammatory lesions that flare unpredictably. The impact of weekly adalimumab (ADAew) on HS flare is not well‐characterized. Objective: To evaluate the impact of disease flare on health‐related quality of life (HRQOL) in moderate‐to‐severe HS patients and to determine the effect of ADAew on disease flare using integrated data from two phase 3 trials over 36 weeks. Methods: In period A (12 weeks), Dermatology Life Quality Index (DLQI) score change from baseline was compared in patients who flared and those who did not, regardless of treatment. The proportion of patients experiencing flare, duration of flare and time to flare was evaluated for ADAew vs. placebo (PBO). In period B (24 weeks), proportion of patients experiencing flare who received continuous ADAew treatment through 36 weeks was assessed. Results: HRQOL was markedly improved among those who did not experience flare. In period A, the proportion of patients who experienced flare was significantly lower with ADAew vs. PBO (12.3% vs. 35.3%, P < 0.001). ADAew patients also had longer time to first flare (101 days vs. 57 days; P < 0.001) and shorter flare duration (18.9 days vs. 32.0 days, respectively; P = 0.001) vs. PBO. Through 36 weeks of treatment, 20.2% of ADAew patients flared, and for those who achieved at least a partial clinical response to ADAew at 12 weeks, only 5.7% flared. Conclusions: Flare reduction is an important measure in HS that correlates with clinically meaningful improvement in HRQOL. ADAew reduces HS flare through 12 and subsequent 36 weeks of treatment.